2021
DOI: 10.1016/j.ijrobp.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

No Longer a Match: Trends in Radiation Oncology National Resident Matching Program (NRMP) Data from 2010-2020 and Comparison Across Specialties

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Other studies used the data reported by the NRMP Charting Outcomes in the Match to draw conclusions about research output among medical students before they matriculated to radiation oncology residency programs. 4 , 5 By manually reviewing various database records, we were able to distinguish peer-reviewed publications from all other research activities in the NRMP data, enabling us to collect more detailed information and draw more robust conclusions about the role of research in the radiation oncology match.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies used the data reported by the NRMP Charting Outcomes in the Match to draw conclusions about research output among medical students before they matriculated to radiation oncology residency programs. 4 , 5 By manually reviewing various database records, we were able to distinguish peer-reviewed publications from all other research activities in the NRMP data, enabling us to collect more detailed information and draw more robust conclusions about the role of research in the radiation oncology match.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Although the number of radiation oncology residency spots has grown and the number of applicants for those spots has declined in recent years, the National Resident Matching Program (NRMP) indicates that the quality of successful matriculants into radiation oncology (defined by routinely reported NRMP metrics) has improved. 2 , 3 , 4 , 5 Aspects considered by residency programs when inviting applicants for interviews include the United States Medical Licensing Examination (USMLE) Step 1 score, letters of recommendation, medical school grades, and involvement in research, with 73% of radiation oncology program directors citing research as an important factor. 6 According to a 2020 report from the NRMP titled Charting Outcomes in the Match , senior year U.S. medical school candidates who matched successfully into radiation oncology reported an average number of 18.3 publications on their Electronic Residency Application Service (ERAS) submission, which is much higher than the 6.9 reported for all matched U.S. medical school seniors.…”
Section: Introductionmentioning
confidence: 99%
“…As workforce diversification efforts expand, periodic review of the ASTRO student membership demographics for ongoing assessment and adaptation, as appropriate, of diversity-, equity-, and inclusion-oriented interventions would be valuable. Finally, in the current climate of the radiation oncology match, 29 , 30 , 31 where fewer students are interested in pursuing radiation oncology, it is particularly important that all radiation oncologists who interact with any medical students are prepared to provide objective, informed, and transparent advice to students still deciding on a career path and support those with an interest in pursuing radiation oncology.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, whether these findings are a result of increasing emphasis on diversity, equity, and inclusion from individual institutions or larger organizations like ASTRO, shifting specialty interest across demographics, or some combination therein cannot be determined. 29 , 30 , 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…6 Other speculative concerns include declining physician salaries with a shift away from employment in private practice and toward large academic medical centers. 7 Current workforce concerns related to job opportunities and prospects for future employment highlight a steadily growing pessimism about the future of our specialty, reflected in the fact that radiation oncology has rapidly gone from being one of the most competitive to one of the least competitive fields among US medical school graduates applying for residency positions. 8 Although causes for this decline are likely multifactorial, any health care trend that may act to further alter employment opportunities, with implications for job satisfaction, requires our attention as a specialty.…”
mentioning
confidence: 99%